If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -2x = 2x + 2 Reorder the terms: 18 + -2x = 2 + 2x Solving 18 + -2x = 2 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 18 + -2x + -2x = 2 + 2x + -2x Combine like terms: -2x + -2x = -4x 18 + -4x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 18 + -4x = 2 + 0 18 + -4x = 2 Add '-18' to each side of the equation. 18 + -18 + -4x = 2 + -18 Combine like terms: 18 + -18 = 0 0 + -4x = 2 + -18 -4x = 2 + -18 Combine like terms: 2 + -18 = -16 -4x = -16 Divide each side by '-4'. x = 4 Simplifying x = 4
| (y+5)(y^2-5y+25)= | | 1+6x-3x=19 | | 3x+35=13x-56 | | 4*1/2-1/3 | | 6x+17=65+3x | | (3x+30)= | | (x+-7)(x+-7)=14x | | 2(a-2)=-(a-1)/(a-4) | | X^2(5x+3)=26x | | 4x-4=2x+14 | | 1/3+2x=5/12 | | 8X-5Y-3=0 | | 50=9x+5 | | 3(2x-1)=2(4x-7) | | 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 | | 56=24(1/6z+5/6) | | 8x=27-x | | H=-16t^2+72t+3 | | -38.5=4.3z-4.1 | | 2x+4-3x=9 | | 24-2x=-6x+4 | | 2x+6-5x=-3 | | 3.1=1.3+2.9 | | 16=20(1/5z+4/5) | | H=-16t+72t+3 | | 5x+2-3x=-2 | | (X+4)(5x-1)=0 | | 3x+6-4x=8 | | a^2=135+6a |